Activity of antimicrobial peptides and conventional antibiotics against superantigen positive Staphylococcus aureus isolated from patients with atopic dermatitis - Błażewicz, Izabela; Jaśkiewicz, Maciej; Piechowicz, Lidia; Neubauer, Damian; Nowicki, Roman; Kamysz, Wojciech; Barańska-Rybak, Wioletta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : Staphylococcus aureus causes a diverse array of diseases, ranging from relatively harmless localized skin infections to life-threatening systemic conditions. It secretes toxins directly associated with particular disease symptoms. Aim : To determine the prevalence of methicillin-resistant S. aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) colonization among patients with atopic dermatitis and to assess the antimicrobial susceptibility to conventional antibiotics and selected antimicrobial peptides among toxin-producing strains and nonproducing strains. Material and methods : One hundred patients with atopic dermatitis and 50 healthy people were microbiologically assessed for the carriage of S. aureus . Antimicrobial susceptibility tests were performed using the broth microdilution method for conventional antibiotics and antimicrobial peptides (CAMEL, Citropin 1.1, LL-37, Temporin A). Detection of genes lukS/lukF-PV, tst, sea-sed, eta and etb by multiplex PCR was performed. Results : Staphylococcus aureus strains were isolated from the majority of patients, from either the skin (75%) or the anterior nares (73%). Among the conventional antibiotics tested, the highest rates of resistance were observed for ampicillin, daptomycin, lincomycin and erythromycin. Antimicrobial peptides did not show significant diversity in activity. Among MSSA strains greater differentiation of secreted toxins was observed ( sec, eta, pvl, tsst, etb, seb ), while in the group of MRSA strains secretion of 3 toxins ( pvl, eta, seb ) was noted. Conclusions : Antimicrobial resistance continues to evolve. It is important to monitor S. aureus infections. The profile of toxins produced by S. aureus strains is an important consideration in the selection of an antimicrobial agent to treat infections.